BIMBINGAN KELOMPOK DENGAN PETA PIKIRAN DAN SELF-REWARD UNTUK MENINGKATKAN KETERAMPILAN BELAJAR SISWA - Akhtiar Sigit Samseno (Universitas Sebelas Maret, 2017)
The research problem is there are students with low learning skills. Research purposes, (1) describe the implementation of group guidance in schools, (2) describe the skill level of student learning, (3) knowing the effectiveness of group guidance with mind maps and self-reward to learning skills. Experimental research methods, types of design randomized pretest-posttest control group design. Samples totaling 20 students were randomly selected low level of learning skills. The data collection instruments using a scale of learning skills. Analysis using Independent Sample T-test. The results of research (1) group guidance in schools has been done is not yet complete, (2) there is a category of students learning skills are low, (3) group guidance and with a mind map self-reward effectively increase the learning skills of students based on the significance of 0.000 <0.05 and an increase in the experimental group was 24.58%, 1.04% control group. Conclusions of this research, (1) the guidance group has done and has not been not maximal, (2) there is a category of students learning skills are low, (3) group guidance with a mind map and self-reward effectively increase students' learning skills.